Preparation method of multifunctional cuprous oxide-based nano composite antibacterial material
By doping elements such as silver, platinum, cerium, lanthanum, and zinc oxide and titanium oxide, modifying cuprous oxide materials, the problem of insufficient stability and antibacterial effect is solved, and rapid sterilization, durable antibacterial and multifunctional performance is achieved Improvement.
Patent Information
- Application Number
- CN202411069706.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-06
- Publication Date
- 2024-12-17
AI Technical Summary
The existing cuprous oxide materials are prone to oxidation in the air, have poor stability, insufficient antibacterial effect, and have less absorption in the visible light area, making it difficult to achieve a lasting antibacterial effect.
Copper oxide is modified by doping elements such as silver, platinum, cerium, lanthanum, and zinc oxide and titanium oxide semiconductor composite to improve its photocatalytic activity and chemical stability, enhance antibacterial ability, and improve surface through surfactant modification Activity, enhances response to visible light and antibacterial properties.
The ability of cuprous oxide materials to quickly sterilize, last long-term antibacterial, anti-mold, remove formaldehyde and degrade wastewater is achieved, improving its chemical stability and antibacterial durability, and simplifying the preparation process and raw material sources.
Smart Images

Figure CN119140115A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano cuprous oxide preparation, in particular to a method for preparing a multifunctional cuprous oxide-based nano composite antibacterial material. Background Art
[0002] Bacteria are ubiquitous in our daily lives and are one of the microorganisms that are in close contact with humans. Generally speaking, the long diameter of bacteria is about 0.5-5.0 μm, and the short diameter is about 0.5-1.0 μm. According to their basic appearance, they can be divided into: cocci, bacilli, spiral bacteria, etc.; according to different cell wall structures, they can be divided into: Gram-negative bacteria, Gram-positive bacteria, etc. Generally, most bacteria are harmless to the human body under normal circumstances, and humans often use bacteria, such as making rice wine, cheese and yogurt, etc.; however, some bacteria are pathogens of many diseases and can spread diseases between humans through various means, such as contact, digestive tract, respiratory tract, insect bites, etc. They are highly contagious and pose a great threat to society. For example, in the 1340s and 1350s, the "Black Death" caused by Yersinia pestis swept across Europe, killing 25 million Europeans; "smallpox" in Mexico caused nearly 3 million deaths; from 1918 to 1919, the Spanish flu killed nearly 50 million people and indirectly ended the First World War; another example is dysentery caused by Shigella flexneri infection, which is transmitted through contact, food and water, resulting in the death of about 1.5 million people each year; the new coronavirus (COVID-19) has infected more than 50 million people in 211 countries around the world, with more than 120,000 deaths. Therefore, even in today's society where science and technology are developing rapidly, the research on antibacterial materials that control the growth and reproduction of pathogenic bacteria is still a vital task closely related to human health. Therefore, new, green and efficient antibacterial materials have emerged, and the development and utilization of such materials has gradually become a research hotspot for scientific researchers.
[0003] Inorganic antibacterial materials refer to a new type of functional materials that have the ability to inhibit or kill surface bacteria by adding certain antibacterial substances (called antibacterial agents). The main antibacterial agents include metal ions such as silver, copper, and zinc and their oxides. Compared with the limited sources of natural antibacterial materials, high extraction costs, poor stability of extracts, and difficulty in large-scale production, inorganic antibacterial materials have the advantages of stable properties and cheap materials; compared with the shortcomings of organic antibacterial materials, such as strong toxicity, poor heat resistance, easy decomposition and volatility, long-term use, easy to make bacteria resistant, and the antibacterial effect gradually weakened or even completely disappeared, inorganic antibacterial materials have broad-spectrum and long-lasting antibacterial properties, high temperature resistance, and will not make bacteria resistant during use. However, some inorganic antibacterial materials have the disadvantages of poor stability and short antibacterial time. As long as these shortcomings are overcome, the research on inorganic antibacterial materials will become the main development direction in the antibacterial field in the future.
[0004] Cuprous oxide is an inorganic metal oxide material. In the past few decades, it has become one of the most intensively studied binary transition metal oxide crystals. Since its antibacterial effect is second only to silver oxide, and it is relatively low in cost, it is often used in the antibacterial field. Cu2O is a common P-type semiconductor with a band gap of about 2.20 eV. It is abundant in the earth and is very environmentally friendly. It is non-toxic, low-cost, easy to prepare, has a narrow band gap, and can absorb visible light. It is a very promising semiconductor photocatalytic material with very important research significance. However, there are currently only a few methods to prepare stable Cu2O. Even if it is stored in an inert gas, it will oxidize as long as it is exposed to air. Although Cu2O has good antibacterial properties, Cu 2+ The release rate is fast, it is difficult to achieve a lasting antibacterial effect and the absorption in the visible light region is low. A large number of studies have shown that doping and semiconductor composites can improve the stability of semiconductors and the photocatalytic conversion efficiency. Summary of the invention
[0005] In view of the above-mentioned prior art, the present invention provides a method for preparing a multifunctional cuprous oxide-based nanocomposite antibacterial material, which has a good effect of removing residual formaldehyde, and has the capabilities of rapid sterilization, long-lasting antibacterial, mildew prevention, formaldehyde removal, and wastewater degradation.
[0006] In order to solve the above technical problems, the present invention proposes a method for preparing a multifunctional cuprous oxide-based nanocomposite antibacterial material, comprising the following steps:
[0007] Step 1, adding copper salt and deionized water into a reaction kettle at a mass volume ratio of 2.5-5g / 100mL, heating and stirring evenly, adding an appropriate amount of surfactant, slowly dropping an appropriate amount of pH regulator, and obtaining solution A after reaction; the pH value of solution A is 9-10, and the mass ratio of the surfactant to the copper salt is 1-4g:10g;
[0008] Step 2, adding a reducing agent to the solution A to obtain a solution B, and continuing to stir until the precipitate turns brick red; the mass ratio of the reducing agent to the copper salt is 0.1-0.25 g:1 g;
[0009] Step 3, adding zinc salt, titanium salt, silver salt, platinum salt, cerium salt and lanthanum salt to the solution B, and continuing stirring to obtain solution C; wherein the molar percentage of the zinc salt to the copper salt is 10-30%, the molar ratio of the titanium salt to the copper salt is 10-30%, the molar percentage of the silver salt to the copper salt is 1-5‰, the molar percentage of the platinum salt to the copper salt is 1-5‰, the molar percentage of the cerium salt to the copper salt is 1-5%, and the molar percentage of the lanthanum salt to the copper salt is 1-5%;
[0010] Step 4, adding a pH adjuster to solution C and continuing stirring to obtain solution D, wherein the pH value of solution D is 9-10; solution D is cooled to room temperature, taken out and filtered to obtain a precipitate; the precipitate is placed in a vacuum drying oven and dried to obtain a multifunctional cuprous oxide-based nanocomposite antibacterial material.
[0011] Furthermore, the preparation method of the present invention, wherein:
[0012] In step 1, the copper salt is one or more of copper sulfate pentahydrate, copper chloride dihydrate, and copper nitrate; the surfactant is one or more of polyvinyl pyrrolidone, polyethylene glycol, ethylenediaminetetraacetic acid, trisodium citrate, and triethanolamine; the pH adjuster is one or more of ammonia water, sodium hydroxide, sodium bicarbonate, potassium hydroxide, ammonium hydroxide, and calcium hydroxide; the heating temperature is 45-60° C., and the reaction time is 120-180 min.
[0013] In step 2, the reducing agent is one of L-ascorbic acid, glucose, hydrazine hydrate and triethanolamine.
[0014] In step 3, the zinc salt is one or more of anhydrous zinc acetate, zinc acetate dihydrate, zinc chloride, and zinc sulfate; the titanium salt is titanyl sulfate; the silver salt is one or more of silver nitrate and silver acetate; the platinum salt is one or more of platinum nitrate and chloroplatinic acid; the cerium salt is one or more of cerium nitrate hexahydrate and cerium chloride; the lanthanum salt is one or more of lanthanum nitrate hexahydrate, lanthanum chloride, and lanthanum sulfate; and the stirring is continued for 60 to 90 minutes.
[0015] In step 4, the pH adjuster is one or more of ammonia water, sodium hydroxide, sodium bicarbonate, potassium hydroxide, ammonium hydroxide, and calcium hydroxide; the stirring time is continued for 60 to 90 minutes; the vacuum drying oven drying temperature is 50 to 60° C., and the drying time is 600 to 800 minutes.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] (1) Cuprous oxide is modified by doping with silver, platinum, cerium, lanthanum and other elements and by combining zinc oxide and titanium oxide semiconductors. The synergistic effect of silver, platinum, cerium, lanthanum, silver and other elements with copper promotes the effective separation of photogenerated electrons and holes in cuprous oxide, effectively enhances the photocatalytic activity of cuprous oxide, and improves the antibacterial ability of nano zinc oxide. Composite semiconductor zinc oxide and titanium oxide improve the chemical stability and antibacterial durability of cuprous oxide while improving the photocatalytic activity.
[0018] (2) By modifying cuprous oxide by doping with elements such as silver, platinum, cerium, and lanthanum, as well as by composite zinc oxide and titanium oxide semiconductors, an intermediate energy level can be established between the valence band (VB) and the conduction band (CB), thereby reducing the band gap and achieving response to the visible light band, thereby effectively improving the photocatalytic activity, thereby improving the anti-mildew ability of nano-cuprous oxide, and at the same time improving the utilization rate of sunlight, thereby improving the formaldehyde degradation ability of nano-cuprous oxide and the ability to degrade sewage and wastewater.
[0019] (3) The surface activity of nano-cuprous oxide is improved by modifying the photocatalytic antibacterial material with surfactants, so that the photo-nano-cuprous oxide can maintain long-term antibacterial, anti-mildew, formaldehyde degradation and antiviral capabilities.
[0020] (4) The preparation process of the present invention is simple, the raw material source is abundant, and it has excellent application prospects.
[0021] (5) The present invention is easy to use. When added to the coating, it can not only be used as a colorant to make the base material have excellent antibacterial, anti-mildew and formaldehyde removal properties, but also can be produced according to the original production process without adding cumbersome processes. In the field of ship antifouling coatings, the invention forms a thin layer of antifouling solution on the surface of the paint film, which can reduce the activation effect of the main enzyme in the biological body on the biological life metabolism, thereby shortening the biological life span, and can coagulate the protein in the biological body, thereby achieving the purpose of antifouling. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a flow chart of the preparation method of the multifunctional cuprous oxide-based nanocomposite antibacterial material of the present invention;
[0023] Figure 2It is the degradation rate of methylene blue within 180 min of samples 1-3 prepared in Examples 1-3 respectively. DETAILED DESCRIPTION
[0024] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but the following embodiments are by no means intended to limit the present invention in any way.
[0025] Example 1
[0026] A method for preparing a multifunctional cuprous oxide-based nanocomposite antibacterial material, such as Figure 1 As shown, the following steps are included:
[0027] Step 1, 5 g (20 mmol) of copper sulfate pentahydrate was placed in 100 ml of deionized water, stirred at 60° C., and 0.75 g of PEG was added to the solution, and then sodium hydroxide was gradually added dropwise to the solution to adjust the pH to 10, and the reaction was continued with stirring for 120 min to obtain solution A;
[0028] Step 2, add 0.6 g of L-ascorbic acid to solution A, and continue stirring until the precipitate turns brick red to obtain solution B;
[0029] Step 3, add 0.438 g (2 mmol) of zinc acetate dihydrate, 0.32 g (2 mmol) of titanyl sulfate, 0.0034 g (0.02 mmol) of silver nitrate, 0.00638 g (0.02 mmol) of platinum nitrate, 0.434 g (1 mmol) of cerium nitrate hexahydrate and 0.2598 g (0.6 mmol) of lanthanum nitrate hexahydrate to solution B, continue stirring and reacting for 60 min to obtain solution C;
[0030] Step 4, gradually add sodium hydroxide solution to solution C to adjust the pH to 10, and continue stirring the reaction for 60 minutes; cool to room temperature, filter out water to obtain a precipitate, and place the precipitate in a vacuum drying oven at 50°C for 600 minutes to obtain a multifunctional cuprous oxide-based nanocomposite antibacterial material, recorded as sample 1.
[0031] Example 2
[0032] A method for preparing a multifunctional cuprous oxide-based nanocomposite antibacterial material, comprising the following steps:
[0033] Step 1, 3.76 g (20 mmol) of copper nitrate was placed in 100 ml of deionized water, stirred at 60°C, and 1.25 g of PVP was added to the solution, and then ammonia was gradually added to the solution to adjust the pH to 10, and the reaction was continued by stirring for 150 min to obtain solution A;
[0034] Step 2, add 0.8 g of glucose to solution A, and continue stirring until the precipitate turns brick red to obtain solution B;
[0035] Step 3, add 0.732 g (4 mmol) of anhydrous zinc acetate, 0.96 g (6 mmol) of titanyl sulfate, 0.0102 g (0.06 mmol) of silver nitrate, 0.0319 g (0.1 mmol) of platinum nitrate, 0.2604 g (0.6 mmol) of cerium nitrate hexahydrate and 0.433 g (1 mmol) of lanthanum nitrate hexahydrate to solution B, continue stirring and reacting for 60 min; obtain solution C;
[0036] Step 4, gradually add ammonia water to solution C to adjust the pH to 10, and continue to stir the reaction for 90 minutes; cool to room temperature, filter out the water to obtain a precipitate, and place the precipitate in a vacuum drying oven at 50°C and dry it for 680 minutes to obtain a multifunctional cuprous oxide-based nanocomposite antibacterial material, recorded as sample 2.
[0037] Example 3
[0038] A method for preparing a multifunctional cuprous oxide-based nanocomposite antibacterial material, comprising the following steps:
[0039] Step 1, 3.41 g (20 mmol) of cupric chloride dihydrate was placed in 100 ml of deionized water, stirred at 55° C., and 1.2 g of trisodium citrate was added to the solution, and then sodium bicarbonate solution was gradually added dropwise to the solution to adjust the pH to 9, and the reaction was continued for 180 min to obtain solution A;
[0040] Step 2, add 0.5 g of hydrazine hydrate to solution A, and continue stirring until the precipitate turns brick red, which is recorded as solution B;
[0041] Step 3, add 1.314 g (6 mmol) of zinc acetate dihydrate, 0.64 g (4 mmol) of titanyl sulfate, 0.0068 g (0.04 mmol) of silver nitrate, 0.02552 g (0.08 mmol) of platinum nitrate, 0.434 g (1 mmol) of cerium nitrate hexahydrate and 0.0866 g (0.2 mmol) of lanthanum nitrate hexahydrate to solution B, continue the reaction for 60 min, and obtain solution C;
[0042] Step 4, gradually add sodium bicarbonate solution to solution C to adjust the pH to 9, and continue the reaction for 90 minutes; cool to room temperature, filter out water to obtain a precipitate, place the precipitate in a vacuum drying oven at 50°C and dry it for 720 minutes to obtain a multifunctional cuprous oxide-based nanocomposite antibacterial material, recorded as sample 3.
[0043] Comparative Example 1
[0044] Compared with Example 1, the only difference is that the metal salt added in step 3 is changed from 0.438 g of zinc acetate dihydrate, 0.32 g of titanyl sulfate, 0.0034 g of silver nitrate, 0.00638 g of platinum nitrate, 0.434 g of cerium nitrate hexahydrate and 0.2598 g of lanthanum nitrate hexahydrate to: 0.32 g of titanyl sulfate, 0.0034 g of silver nitrate, 0.00638 g of platinum nitrate, 0.434 g of cerium nitrate hexahydrate and 0.2598 g of lanthanum nitrate hexahydrate, that is, zinc acetate dihydrate is not added; the multifunctional cuprous oxide-based nanocomposite antibacterial material finally obtained is recorded as comparison sample 1.
[0045] Comparative Example 2
[0046] Compared with Example 1, the only difference is that the metal salt added in step 3 is changed from 0.438 g of zinc acetate dihydrate, 0.32 g of titanyl sulfate, 0.0034 g of silver nitrate, 0.00638 g of platinum nitrate, 0.434 g of cerium nitrate hexahydrate and 0.2598 g of lanthanum nitrate hexahydrate to: 0.438 g of zinc acetate dihydrate, 0.0034 g of silver nitrate, 0.00638 g of platinum nitrate, 0.434 g of cerium nitrate hexahydrate and 0.2598 g of lanthanum nitrate hexahydrate, that is, no titanyl sulfate is added; the multifunctional cuprous oxide-based nanocomposite antibacterial material is finally obtained and recorded as comparison sample 2.
[0047] Comparative Example 3
[0048] Compared with Example 1, the only difference is that the metal salt added in step 3 is changed from 0.438 g of zinc acetate dihydrate, 0.32 g of titanyl sulfate, 0.0034 g of silver nitrate, 0.00638 g of platinum nitrate, 0.434 g of cerium nitrate hexahydrate and 0.2598 g of lanthanum nitrate hexahydrate to: 0.438 g of zinc acetate dihydrate, 0.32 g of titanyl sulfate, 0.434 g of cerium nitrate hexahydrate and 0.2598 g of lanthanum nitrate hexahydrate, that is, no silver nitrate and platinum nitrate are added; the multifunctional cuprous oxide-based nanocomposite antibacterial material is finally obtained and recorded as comparison sample 3.
[0049] Comparative Example 4
[0050] Compared with Example 1, the only difference is that the metal salt added in step 3 is changed from 0.438 g of zinc acetate dihydrate, 0.32 g of titanyl sulfate, 0.0034 g of silver nitrate, 0.00638 g of platinum nitrate, 0.434 g of cerium nitrate hexahydrate and 0.2598 g of lanthanum nitrate hexahydrate to: 0.438 g of zinc acetate dihydrate, 0.32 g of titanyl sulfate, 0.0034 g of silver nitrate, 0.00638 g of platinum nitrate, that is, no cerium nitrate and lanthanum nitrate are added; the multifunctional cuprous oxide-based nanocomposite antibacterial material is finally obtained and recorded as comparison sample 4.
[0051] Comparative Example 5
[0052] Compared with Example 1, the only difference is that step 3 is not performed, that is, zinc acetate, titanyl sulfate, silver nitrate, platinum nitrate, lanthanum nitrate and cerium nitrate are not added, and the multifunctional cuprous oxide-based nanocomposite antibacterial material finally prepared is recorded as comparison sample 5.
[0053] Comparative Example 6
[0054] Compared with Example 1, the only difference is that the surfactant PEG is not added in step 1, and the multifunctional cuprous oxide-based nanocomposite antibacterial material finally prepared is recorded as comparative sample 6.
[0055] Comparative Example 7
[0056] Compared with Example 1, the difference is that step 2 is not performed, that is, the reducing agent L-ascorbic acid is not added; the multifunctional cuprous oxide-based nanocomposite antibacterial material finally prepared is recorded as comparative sample 7.
[0057] Performance Testing
[0058] The samples prepared in Examples 1-3 and / or Comparative Examples 1-7 were subjected to multifunctional performance tests, including experiments on antibacterial, anti-aging, antibacterial persistence, antiviral, anti-mildew, formaldehyde removal and wastewater degradation capabilities.
[0059] (1) Antibacterial test
[0060] According to the national standard "Test Method for Antibacterial Performance of Nano-inorganic Materials GB / T 21510-2008", 0.1 mg of samples prepared in Examples 1-3 and Comparative Examples 1-7 were weighed and sterilized for 40 minutes using an ultraviolet sterilization lamp in a clean bench. The bacterial solution cultured for 16 hours was diluted by 3 orders of magnitude, and the multifunctional cuprous oxide-based nano-composite antibacterial material after disinfection was added, and the mixture was placed in a shaker at a temperature of 37°C and a speed of 150 rpm for 1 hour. 100 μL of the shaken bacterial solution was taken, inoculated on a culture dish, and placed in a constant temperature and humidity incubator at a temperature of 37°C and a relative humidity of 90% for 24 hours to count the viable bacteria. The results are shown in Table 1.
[0061] Table 1
[0062] sample Escherichia coli antibacterial rate (%) Antibacterial rate of Staphylococcus aureus (%) Sample 1 100 100 Sample 2 100 100 Sample 3 100 100 Comparison sample 1 83.69 85.61 Comparison sample 2 86.26 88.85 Comparison sample 3 75.81 76.37 Comparison sample 4 81.86 85.36 Comparison sample 5 69.35 73.69 Comparison sample 6 72.58 76.57 Comparison sample 7 55.23 58.23
[0063] It can be seen from Table 1 that the multifunctional cuprous oxide-based nano-composite antibacterial material of the present invention has excellent antibacterial properties, and the sterilization rates against Escherichia coli and Staphylococcus aureus can reach 100%.
[0064] (2) Anti-aging test
[0065] The samples prepared in Examples 1-3 and Comparative Examples 1-7 were placed at 50°C for 16 hours for accelerated aging treatment. After drying, 0.1 mg of each sample was weighed and sterilized for 40 minutes using an ultraviolet sterilization lamp in a clean bench. The bacterial solution cultured for 16 hours was diluted by 3 orders of magnitude, and the multifunctional cuprous oxide-based nanocomposite antibacterial material after disinfection was added, and placed in a shaker at a temperature of 37°C and a speed of 150 rpm for 1 hour. 100 μL of the shaken bacterial solution was taken, inoculated on a culture dish, and placed in a constant temperature and humidity incubator at a temperature of 37°C and a relative humidity of 90% for 24 hours to count the live bacteria. The results are shown in Table 2.
[0066] Table 2
[0067] sample Escherichia coli antibacterial rate (%) Antibacterial rate of Staphylococcus aureus (%) Sample 1 100 100 Sample 2 100 100 Sample 3 100 100 Comparison sample 1 75.86 82.89 Comparison sample 2 81.25 84.59 Comparison sample 3 72.93 74.82 Comparison sample 4 76.59 81.24 Comparison sample 5 50.28 65.29 Comparison sample 6 69.25 71.27 Comparison sample 7 52.54 56.71
[0068] It can be seen from Table 2 that the multifunctional cuprous oxide-based nanocomposite antibacterial material of the present invention has excellent anti-aging performance, and the sterilization rates of Escherichia coli and Staphylococcus aureus can reach 100% after aging treatment.
[0069] (3) Antibacterial persistence test
[0070] The samples prepared in Examples 1-3 and Comparative Examples 1-7 were added to the PBS solution and shaken at 37°C for 0, 1, 2, 3, 7, 14, 21, and 28 days, and the dried powders were tested for antibacterial persistence. 0.1 mg of the samples prepared in Examples 1-3 and Comparative Examples 1-7 were weighed and sterilized for 40 minutes using an ultraviolet sterilization lamp in a clean bench. The bacterial solution cultured for 16 hours was diluted by 3 orders of magnitude, and the multifunctional cuprous oxide-based nanocomposite antibacterial material after disinfection was added, and placed in a shaking table at a temperature of 37°C and a speed of 150rpm for 1 hour. 100 μL of the shaken bacterial solution was taken, inoculated on a culture dish, and placed in a constant temperature and humidity incubator at a temperature of 37°C and a relative humidity of 90% for 24 hours to count the viable bacteria. The results are shown in Tables 3 and 4.
[0071] Table 3
[0072]
[0073]
[0074] Table 4
[0075]
[0076] It can be seen from Table 3 and Table 4 that the multifunctional cuprous oxide-based nanocomposite antibacterial material of the present invention has excellent antibacterial durability, and the sterilization rates of Escherichia coli and Staphylococcus aureus can reach more than 95% after immersion for 28 days.
[0077] (4) Antiviral experiments
[0078] The experimental samples are: samples 1-3 prepared in Examples 1, 2, and 3. The experiment refers to Appendix B of GB / T 21510-2008, the experimental virus is: influenza A virus H1N1: A / PR / 8 / 34 (ATCC VR-1469), host name: MDCK cells. The test results are shown in Table 5.
[0079] Table 5
[0080] sample Virus inactivation rate (%) Sample 1 >99.99 Sample 2 >99.99 Sample 3 >99.99
[0081] It can be seen from Table 5 that the multifunctional cuprous oxide-based nanocomposite antibacterial material of the present invention has excellent antiviral performance.
[0082] (5) Anti-mildew test
[0083] Weigh 10g of samples 1-3 prepared in Examples 1, 2, and 3, respectively, and 990g of white paint, respectively, and sterilize them with an ultraviolet sterilization lamp in a clean bench for 40min. The multifunctional cuprous oxide-based nanocomposite antibacterial material was mixed with 990g of white paint and stirred thoroughly to obtain a paint with a sample content of 1%, which was evenly brushed on a 10*10cm PVC sheet. The PVC sheet was placed in a cool and ventilated place for 48 hours. After the paint on the surface of the PVC sheet was completely solidified, the PVC sheet was placed in an environment of 37°C and 90% relative humidity for 60d, and the growth of mold on the surface was observed. The test results are shown in Table 6.
[0084] Table 6
[0085] sample Mildew resistance level Sample 1 Level 0 Sample 2 Level 0 Sample 3 Level 0
[0086] It can be seen from Table 6 that the multifunctional cuprous oxide-based nanocomposite antibacterial material of the present invention has excellent mildew resistance.
[0087] (6) Formaldehyde removal experiment
[0088] The experimental samples are: mixtures of samples 1-3 prepared in Examples 1, 2, and 3 respectively with white paint, and the sample content is 1%. The experiment refers to JC / T 1074-2021, the experimental time is 24h, the experimental box volume is 1m3, and the test results are shown in Table 7.
[0089] Table 7
[0090] sample Purification efficiency (%) Sample 1 89.7 Sample 2 88.59 Sample 3 87.26
[0091] It can be seen from Table 7 that the multifunctional cuprous oxide-based nanocomposite antibacterial material of the present invention has excellent formaldehyde removal performance.
[0092] (7) Ability to degrade wastewater
[0093] Methylene blue was used to simulate wastewater, and a xenon lamp was used to simulate sunlight. The experimental samples were samples 1-3 prepared in Examples 1, 2, and 3. The sample addition amount was 1000 ppm, and the degradation rate of methylene blue within 180 minutes was tested. The results are as follows Figure 2 As shown, it can be concluded that after only 30 minutes of illumination, the degradation rate of methylene blue by samples 1, 2, and 3 reached about 80%, and after 60 minutes of illumination, the degradation rate reached about 96%, indicating that samples 1, 2, and 3 have excellent photocatalytic degradation performance and optical properties.
[0094] Although the present invention has been described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned specific embodiments, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can make many improvements and changes without departing from the purpose of the present invention, which are all within the protection of the present invention.
Claims
1. A method for preparing a multifunctional cuprous oxide-based nanocomposite antibacterial material. It is characterized in that The following steps are involved: Step 1, adding copper salt and deionized water into a reaction kettle at a mass volume ratio of 2.5-5g / 100mL, heating and stirring evenly, adding an appropriate amount of surfactant, slowly dropping an appropriate amount of pH regulator, and obtaining solution A after reaction; the pH value of solution A is 9-10, and the mass ratio of the surfactant to the copper salt is 1-4g:10g; Step 2, adding a reducing agent to the solution A to obtain a solution B, and continuing to stir until the precipitate turns brick red; the mass ratio of the reducing agent to the copper salt is 0.1-0.25 g:1 g; Step 3, adding zinc salt, titanium salt, silver salt, platinum salt, cerium salt and lanthanum salt to the solution B, and continuing stirring to obtain solution C; wherein the molar percentage of the zinc salt to the copper salt is 10-30%, the molar ratio of the titanium salt to the copper salt is 10-30%, the molar percentage of the silver salt to the copper salt is 1-5‰, the molar percentage of the platinum salt to the copper salt is 1-5‰, the molar percentage of the cerium salt to the copper salt is 1-5%, and the molar percentage of the lanthanum salt to the copper salt is 1-5%; Step 4, adding a pH adjuster to solution C and continuing stirring to obtain solution D, wherein the pH value of solution D is 9-10; solution D is cooled to room temperature, taken out and filtered to obtain a precipitate; the precipitate is placed in a vacuum drying oven and dried to obtain a multifunctional cuprous oxide-based nanocomposite antibacterial material.
2. The preparation method according to claim 1, It is characterized in that In step 1, the copper salt is one or more of copper sulfate pentahydrate, copper chloride dihydrate, and copper nitrate; The surfactant is one or more of polyvinyl pyrrolidone, polyethylene glycol, ethylenediaminetetraacetic acid, trisodium citrate, and triethanolamine; The pH regulator is one or more of ammonia water, sodium hydroxide, sodium bicarbonate, potassium hydroxide, ammonium hydroxide, and calcium hydroxide; The heating temperature is 45-60°C and the reaction time is 120-180 minutes.
3. The preparation method according to claim 1, It is characterized in that In step 2, the reducing agent is one of L-ascorbic acid, glucose, hydrazine hydrate and triethanolamine.
4. The preparation method according to claim 1, It is characterized in that In step 3, the zinc salt is one or more of anhydrous zinc acetate, zinc acetate dihydrate, zinc chloride, and zinc sulfate; the titanium salt is titanyl sulfate; the silver salt is one or more of silver nitrate and silver acetate; the platinum salt is one or more of platinum nitrate and chloroplatinic acid; the cerium salt is one or more of cerium nitrate hexahydrate and cerium chloride; the lanthanum salt is one or more of lanthanum nitrate hexahydrate, lanthanum chloride, and lanthanum sulfate; The reaction time with continued stirring is 60 to 90 minutes.
5. The preparation method according to claim 1, It is characterized in that In step 4, the pH regulator is one or more of ammonia water, sodium hydroxide, sodium bicarbonate, potassium hydroxide, ammonium hydroxide, and calcium hydroxide; The reaction time of continued stirring is 60 to 90 minutes; The vacuum drying oven has a drying temperature of 50-60° C. and a drying time of 600-800 min.
